Pengaruh pengetahuan asas algebra terhadap kemahiran penyelesaian masalah berayat subjek Matematik dalam kalangan pelajar menengah rendah daerah Tatau - Lay, Siong Ming (2011)
The aim of this study is to determine the relationship between the basic knowledge and problem-solving skill on mathematical word problem-solving in Algebraic Expressions among the Form Two students. It also aims to find out the students' basic Algebraic knowledge based on gender. This quantitative study involved 136 Form Two students from a secondary school in Tatau Bintulu. Two types of instruments were used for this study, namely, Basic Knowledge Test and Word Problem-Solving Test in Algebraic Expressions. Researcher used SPSS (Statistical Packages Social Science) version 12 to analyse the collected data. The results of the test show that students have good basic knowledge in Algebraic Expressions, but they are weak in Word Problem-Solving skill in Algebraic Expressions. The results also show that the relationship between basic knowledge and problem-solving skill on mathematical word problem-solving in Algebraic Expressions are positive and significant (r = 0.71, p < 0.01). Besides that, the study shows that there is no positive and significant difference (t = 0.26, p > 0.05) between the gender for basic knowledge in Algebraic Expressions